PENERAPAN PRINSIP TANGGUNG JAWAB MUTLAK (ABSOLUT LIABILITY) BERKAITAN DENGAN KERUGIAN KONSUMEN ATAS PENGGUNAAN PRODUK INTERNET BANKING - Dian Mahardikha (Indonesia Private Law Review, 2020)
Consumers are parties in weaker position than banking business actors, so consumers do not have the power to encourage banking business actors in fulfil their responsibility for losses in the use of internet banking products. This is one of the reasons why the absolut liability principle is very important to apply. This study focuses on issues regarding the implementation of absolut liability related to consumer losses from the use of internet banking products, as well as an analysis of the inhibiting factors of the implementation of absolut liability related to consumer losses from using internet banking products. The method in this research is empirical normative legal research.The results study showed that the principle of absolut liability is difficult to apply if there are consumer losses due to the use of internet banking products. It is because Article 19 paragraph (5) and Article 28 of the Consumer Protection Law and Article 15 paragraph (3) of the Electronic Information and Transaction Law have requirements for the fulfillment of an element of error in a business actor, whereas in the principle of absolut liability the element of an actor's error business is not an absolute requirement that must be met. The most dominant factors related to the application of the principle of absolut liability can not include legal factors, namely the absence of absolut liability arrangements, law enforcement factors, namely the attachment of proof systems to the elements of business actors' mistakes, and community factors as consumers, namely the limitations to demand compliance responsibility to business actors.